Efektivitas Kompres Air Hangat dan Dingin Untuk Mengurangi Rasa Sakit Pada Ibu Infartuari Pada Fase 1 Persalinan Fisiologis Aktif di Ruang Vk RSIA Sitti Khadidjah A Isyiyah Kota Gorontalo - Harismayanti Harismayanti; Dewi Modjo; Yulfa S. Hamid (Lembaga Pengembangan Kinerja Dosen, 2023)
Introduction : Pain in labor is pain due to uterine contractions which can lead to increased activity of the sympathetic nervous system, changes in blood pressure, heart rate, breathing, and if not treated it will increase feelings of worry, tension, fear and stress. Warm and cold water compress therapy is a non-pharmacological method to meet the need for comfort and to treat pain. Objective : to determine the effectiveness of giving warm and cold compresses to reduce pain in active phase 1 infartu mothers at RSIA Siti Khadidjah Aisyiyah, Gorontalo city. Research Methods : One group of subjects will be used in this study with a pre-experimental research design with a one-group pre-post test strategy to determine cause and effect. Before the intervention, the subject group was monitored, and then after the intervention. Mothers who were in the early phase of the active phase of physiological labor in the VK room of RSIA Siti Khadijah Aisyiyah, Gorontalo City, were used as research subjects. Research Results : The results of this study found acute pain in the four patients, it was found that 2 patients were given warm water compresses, the pain level decreased to a pain scale of 4 (moderate) and in the administration of cold water compresses to 2 patients, the pain level decreased to a pain scale of 6 and 5 (currently). Conclusion : the conclusion of this study is seen from the level of pain that has decreased when given warm water or cold water compresses. Hot and cold compress therapy is a non-pharmacological method to treat pain.